Faktor Yang Berkontribusi Terhadap Jumlah Penerimaan Dana Zakat Pada Lembaga Zakat Di Kota Surabaya - Farid Nugroho; Tika Widiastuti (Universitas Airlangga, 2016)
The aim of this study is to determine and analyze the contribution of technological factor, accessibility factor, credibility factor, and programs factor of zakat institutions to the zakat funds revenue received by zakat institutions in Surabaya. This study used a qualitative approach with case study strategy. Data collected through interviews with informants and direct observation to the object of the research. The result of this study is there are several factors that have important contribution to zakat revenue at zakat institution in Surabaya. The researcher found accessibility, credibility and zakat collection program during Ramadhan have important contribution to the revenue of zakat funds, while technology has not been widely used by muzakki to make payment of zakat.